Mesél a keringő… III. rész - Fellegi Ádám műsora
last of a series, musical tastes, relationship of past and present, classical music and disco, playing waltz in a disco, history of waltz, Schubert, Sehnsucht Waltzer, operetta, Bartók The Miraculous Mandarin, Hugo Wolf, Strauss, Zsolt Lengyel